ROLE OF TOCILIZUMAB IN PATIENTS WITH MODERATE-TO-SEVERE COVID-19 PNEUMONIA - SHAH, SHAILA JAY; SHAH, JAY H.; PATEL, RAVI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Cytokine release syndrome (CRS) is believed to be responsible for death in COVID-19. Tocilizumab is an interleukin (IL)-6 receptor antagonist, IL-6 being identified as a major component of the CRS cascade. The objective of the study was to determine if tocilizumab can prevent mortality and morbidity in moderate-to-severe COVID-19 pneumonia. Methods: Patients admitted to the ICU between the time period of June 2020–August 2020 were included in this retrospective and cohort study conducted at GCS medical college, hospital and research center. Patients had to be more than 18 years of age and were required to have a positive reverse transcription polymerase chain reaction report for COVID-19. After applying the inclusion/exclusion criteria, 119 patients were considered for final analysis. Tocilizumab was administered as a single dose of 8 mg/kg in 22 patients. Rest of the patients received standard of care regime. The primary outcome was either discharge or death of the patients and the requirement of invasive mechanical ventilation during their hospital stay. The secondary outcome was the length of hospital stay. Appropriate demographic, clinical, and laboratory data were documented. Statistical analysis was done with appropriate clinical tests with significance set at p<0.05. Results: Tocilizumab significantly reduced deaths in patients as well as the need for mechanical ventilation with NNT=3 and 5, respectively. The same held true even when the data were adjusted for age, gender, and number of comorbidities. Number of comorbidities had a negative association with mortality and need for mechanical ventilation irrespective of administration of tocilizumab as evidenced by multivariable logistic regression. There was no effect of tocilizumab in shortening the hospital stay in patients. Conclusion: Tocilizumab seems to be a promising agent for the treatment of moderate to severe COVID-19 pneumonia and similar agents hold promise for any similar future emerging infections.